A reliability and security enhanced framework for cloud-based storage systems. (30th March 2023) - Xiao, Peng
In cloud computing environments, reliable and secure data storage service plays a more and more important role in many data-intensive applications. However, existing storage systems either fail to provide them or provide them in a cost-ineffective manner. To provide better storage service in nowadays cloud environments, we propose a novel framework called reliability and security enhanced cloud storage (RSCS), which consists of several well-designed components to improve low-level data reliability as well as guarantee up-level data accessing security. In the RSCS framework, a simple yet effective file system scheme is proposed, which can duplicate stripped data in different storage nodes so as to increase the data reliability and aggregated throughput. We also introduce a centralised leasing mechanism, which allows accessing different portions of a file based on the multiple-reader-single-writer principle. Finally, we provide a secure data accessing tunnel technology, which allows the RSCS to establish secure communication channels between users and storage nodes without introducing too many extra costs. In a real-world cloud platform, we conduct sets of experiments and the results show that the proposed RSCS framework is able to meet the requirements for most of cloud-based storage platforms.